Treatment of relapsed/refractory acute myeloid leukaemia in adults. (9th January 2018) - Rashidi, Armin; Weisdorf, Daniel J.; Bejanyan, Nelli
Summary: The prognosis of relapsed acute myeloid leukaemia (AML) is poor and treatment is challenging. While the most potent treatment modality for patients who achieve a complete remission after relapse is still allogeneic haematopoietic cell transplantation (allo‐HCT), both transplant‐related mortality and relapse rates are high and many patients are not candidates for this approach. After a few decades of relative stasis in this field, a large number of novel approaches have become available to tackle this highly fatal disease. This is mostly due to our improved understanding of disease pathogenesis (including targetable mutations) and the anti‐leukaemia potential of the immune system. Several small‐molecule inhibitors and immunotherapeutic options are being explored in clinical trials and many more are in pre‐clinical phase. Future studies will focus on novel and mechanistically driven combinations, sequential treatments, and low‐toxicity maintenance strategies. While cure of relapsed/refractory AML without allo‐HCT is currently unlikely, treatments are becoming less toxic and remissions are lasting longer.